METHODOLOGICAL ASPECTS OF THE TRANSFORMATION OF INTERACTION MARKETING, RELATIONSHIP MARKETING IN THE PROCESSES OF THE DIGITAL ECONOMY - Volodymyr I. Dubnytskyi; Tetiana S. Mishustina; Olha V. Ovcharenko (Êvropejsʹkij Vektor Ekonomìčnogo Rozvitku)
To form a common platform for research on the impact of digital transformation of the economy, theoretical, methodological aspects of interaction marketing and relationship marketing in the system of economic mechanism of enterprises, business entities, it is logical to turn to their genesis, since the economic situation in Ukraine and its regions demonstrates the origins of all modern problems of production and services. The relevance of the topic is due to a wide range of competing marketing concepts, the inconsistency of which has only increased over the past 20 years of the XXI century. The analysis of scientific positions carried out in this work showed their limitations, focus on solving specific problems and insufficiency for the formation of a common research platform. The work sets and substantiates the following tasks of linkage marketing and relationship marketing: aspects of the formation and development of the concept of holistic interaction marketing within the framework of using linkage marketing and relationship marketing (partnership marketing) are considered; the stages of marketing evolution in the context of digitalization are substantiated, components of marketing in authoritarian and market systems are presented; the client-model of the life cycle of relationships with the buyer is shown; the author’s conceptually deployed model of the relationship with the buyer is developed. It also considers a client-model of influence of information technologies upon interaction between a seller and a buyer and reveals discrepancies between the desired and actual degree of satisfaction of the parties with relations, which arise as a result of introduction of an information system when using information and communication technologies, by the method of R. Vlosky and D. Winston. It is concluded that with a certain variety of scientific positions of domestic and foreign scientists, including: H. Hokasin, J. Johansson, K. Gronros, L. Stern and Anne Coughlan, G.L. Bagiev, I.M. Akimova, E. Gumesson, R. McKenna, V.P. Pleskach, N.S. Struk, V.V. Stadnik, T.B. Reshetilova and T.V. Kuvaeva, I.O. Tarlapov, etc. common to all is a value-oriented approach, long-term mutually beneficial cooperation of the enterprise, company, firm with consumers using the tools of interaction marketing, relationship marketing in the process of joint creation of economic value in combination with the formation of consumer utility